Robust HPLC-MS/MS quantification of N-acyl homoserine lactones (AHLs) in biomass-associated solid matrices reveals their aqueous–solid distribution in wastewater treatment systems - Xinhao Xu; Xuejun Bi; Hui Zhang; Boyan Xu; Xueqing Shi; Haifeng Zhang; Lihua Cheng; Xiaolin Zhou; Tang Yang; Kibaek Lee; Shujuan Huang; How Yong Ng (Water Research, 2026)

Multimodal vibration suppression of stay cables using dual negative stiffness dampers: Experimental and analytical investigations - Zhipeng Cheng; Ruisheng Ma; Zhihao Wang; Huan Li; Xiuli Du; Kaiming Bi (Engineering Structures, 2026)

Planar conjugated multidentate malonamide additive for regulating Zn2+ solvation structure and interfacial electric field for zinc-ion batteries - Le Zhang; Shuyu Bi; Xijun Liu; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Dynamic soft-templating of highly polymerized carbon nitride enabling potentiated visible light-driven NH2Cl activation: A synergistic self-amplifying ROS/RNS cascade toward water remediation - Xingbo Yin; Qixun Zou; Yaqi Yong; Xiaowei Huo; Xin Cheng; Yuling Tang; Jiguang Du; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Self-powered vibration online monitoring of power transformers enabled by triboelectric nanogenerator - Qun Deng; Shijie Zhai; Xin Yu; Minghao Zhang; Daiyong Yang; Jingyao Luan; Wei Jiang; Xiangzhuang Bi; Hengyu Li; Tinghai Cheng (Chemical Engineering Journal, 2026)

Modelling phase-transition-driven gas dispersion resulting from supercritical CO2 pipeline leak in complex terrain - Xinhong Li; Changzhi Bi; Cheng Li; Hanyu Liu; Fei Shi; Peihua Liu; Ziyue Han (Process Safety and Environmental Protection, 2026)

Layer‑resolved core-shell hydrogel for in situ fluorescence monitoring of Hg(II) adsorption and removal - Xiaoya Bi; Lijun Luo; Xin Gao; Zixiang Liao; Yue Ren; Cheng Xu; Libo Li; Tianyan You (Journal of Hazardous Materials, 2026)

Pollination niche overlap contributes to the maintenance of rare flowering species in alpine grasslands - Ting Yang; Cheng Bi; Gerardo Arceo-Gómez; Anton Pauw; Erliang Gao; Yuxian Wang; Zhigang Zhao (Oecologia, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

Genetic Parameters and the Influence of Genotype by Environment Interactions on Growth Traits in Crassostrea gigas - Geng Cheng; Zhenzong Pan; Shulei Jin; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

Bionic nanozyme arrays for selective identifying and discriminating sulfonylurea herbicides via recognition site mimicry - Yuqing Cheng; Tian Tian; Donghui Song; Yu Ma; Zhichun Bi; Xinjian Zhang; Ling Zhang; Yongxin Li; Hui Huang (Journal of Hazardous Materials, 2026)

UAV coarse visual localization in large-scale continuous scenes - Cheng Bi; Jingfeng Wang; Zhengxi Li; Yang Zhao; Zhiyu Jiang; Yuan Yuan; Ganchao Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

The interactive effects of impervious surface, vegetation, and water on urban land surface temperature - Yangcen Zhang; Caiyan Wu; Jiong Wu; Xing Bi; Meng Wang; Linke Ouyang; Cheng Li; Conghe Song; Feng Mao; Dagmar Haase; Maros Finka; Cristian Ioan Iojă; et al. (Sustainable Cities and Society, 2026)

Temperature-disease network reveals global health risks of climate change - Weican Zhang; John S. Ji; Cunrui Huang; Cheng Qian; Binghao Jia; Haidong Kan; Tiantian Li; Weiqi Zhou; Yuhai Bi; Qian Liu; Guibin Jiang (Science Bulletin, 2026)

Seven previously undescribed seco-abietane and seco-isopimarane type diterpenoids from Biscogniauxia sp. and their biological activities - Meng Zhang; Yang Yan; Wen-Song Bi; Liu-Yang Ma; Dan Hu; Liang-Dong Guo; Zuo-Cheng Qiu; Guo-Dong Chen; Huan Zhao; Hao Gao (Phytochemistry, 2026)

Influence of suspended particulate matter input on phytoplankton community structure in estuarine environments - Xinjie Wang; Yimei Xi; Kuo Fang; Cheng Li; Yongbin Li; Shaofeng Wang; Ran Bi; Zhanyou Chi; Jiashen Tian; Xiangfeng Zeng (Marine Environmental Research, 2026)

Beauvericin modulates immune responses in the silkworm, Bombyx mori: insights from cellular and transcriptomic analyses - Jinhua Fan; Yong Bi; Jia Li; Hui Su; Aiying Cheng; Baozhen Li (Journal of Invertebrate Pathology, 2026)

Electrochemical engineering in situ induces highly thermodynamically stable interface toward long-life zinc metal anodes - Min Lin; Le Zhang; Xijun Liu; Shuyu Bi; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

Origins of Miocene basaltic magmatism in the western Yarlung-Tsangpo Suture Zone, southern Tibet: Insight into the lateral and longitudinal tearing of the subducted Indian continental slab - Jianbo Cheng; Xianshu Dong; Yalin Li; Shuai Li; Siqi Xiao; Wenjun Bi; Rui Zhou (Chemical Geology, 2026)

Evaluating the impact of biochar and fibers on the permeability and microstructural characteristics of silt - Jinmei Dong; Qi Cheng; Yinqiu Xu; Gang Bi; Hongzhong Xu; Qian Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Cordycepin inhibits human extravillous trophoblast invasion by suppressing snail-mediated MMP2 expression - Manman Guo; Siwei Luo; Beibei Bi; Xiaoyu Han; Yuanyuan Jia; Jung-Chien Cheng; Lanlan Fang (Tissue and Cell, 2026)

Coupled geometric and mooring non-linearities in a non-wave-riding FPV system: An experimental study - Jianjun Chen; Hua-Dong Zheng; Yu Lei; Xun Xu; Ruichao Liu; Cheng Bi; Hongbo Zhang; Bin Wu (Ocean Engineering, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Preparation of high mechanical strength adsorption materials by co-pyrolysis of low-polysaccharide lignin, crude oil and clay: the adsorption characteristics of oil and heavy metals in water - Jie Zhang; Yaozhong Zhang; Wangyuan Zhang; Weiyu Bi; Wen Cheng; Ke Dong; Wei Lv; Sanbao Dong (Biomass and Bioenergy, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Effects of dietary chitosan oligosaccharide on juvenile grass carp: Insight from the intestinal microbiota and metabolism - Yong Dou; Liuyang Cheng; Guihai Yu; Peize Li; Hongxu Cao; Xiangdong Bi; Wenli Zhou (Journal of Fish Biology, 2026)
Nowadays, chitosan oligosaccharide (COS) served as a feed additive has been gradually applied to aquaculture. In aims to reveal the effects of COS on the growth intestinal microbiota and metabolism of Grass carp, this experiment using the feed with 3% COS supplement was conducted. The results indicated that the growth indicators (WGR and SGR) of Grass carp were promoted significantly ( p Cetobacterium , Plesiomonas and Brevinema were enriched in the COS treatment, and the intestinal microbiota profile was improved through increasing the abundance of beneficial bacteria ( Cetobacterium ). Besides, a series of lysophosphatidylcholine (LPC) (LPC 16:2, LPC 14:0, LPC 19:2, LPC 19:1, LPC O‐16:2), lysophosphatidylethanolamine (LPE) (LPE 16:2 and LPE O‐16:2) and a butanoic acid derivative named 3‐[4‐methyl‐1‐(2‐methylpropanoyl)‐3‐oxocyclohexyl]butanoic acid were up‐regulated, and two long chain fatty acyl‐CoA (LPG) (LPG 20:2 and LPG 18:0) and LPS 20:3 belonging to lipopolysaccharide (LPS) down‐regulated in the COS treatment. Therefore the result implied that the intestinal health of Grass carp would be protected via reducing the LPS induced the intestinal oxidative stress and inflammatory injury in fish. The metabolic pathways enriched in the profile between the COS treatment and control were mainly concentrated on lipid and derivative metabolism, amino acid metabolism, carbohydrate metabolism and ones associated to the signal transduction. Based on the correlation analysis, butanoic acid was identified as the metabolic marker related to Cetobacterium and Plesiomonas , while LPC O‐16:2 was determined as the biomarker associated to Brevinema. Therefore, the application of COS gives promising results and will be a green feed additive in aquaculture.

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

Metal-node-dependent lubrication performance and tribochemistry of mono- and bimetallic MOF-based additives - Xiao Cheng; Bingxiang Liu; Kuiliang Gong; Feiyang Xu; Ge Zhang; Haoan Bi; Shukang Nan; Bin Li; Xinhu Wu (Chemical Engineering Journal, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Anchoring free chlorine on carbon nanotubes to drive nonradical oxidation: interfacial binding-mediated complex generation enabling contaminant abatement - Qixun Zou; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Intestinal NEDD4L Signaling Inhibiting Carbon Tetrachloride-Induced Liver Fibrosis in Mice Involves Gut Lactobacillus Orchestrating Type 1 Interferon Expression - Junyan Gao; Yanghui Bi; Bangtao Chen; Song He; Cheng Chen (Indian Journal of Microbiology, 2026)
Liver fibrosis (LF), characterized by hepatic stellate cell (HSC) activation and linked to an imbalance of gut microbiota or organismal type 1 interferon (IFN1) at steady state, was demonstrated to be aggravated by the global deletion of neural precursor cell-expressed developmentally down-regulated 4-like ( Nedd4L ) in our previous work. To uncover the role of cell-type specific NEDD4L in LF and its relationship to the gut microbiota/IFN1 axis, intraperitoneal injection of carbon-tetrachloride (CCL4) was used to induce LF in adult female C57BL/6J mice with conditional knockout (cKO) of Nedd4L in hepatocytes, HSC or intestinal epithelial cells (IEC). Fibrotic mice were simultaneously treated with intragastric bacteria or intraperitoneal IFNα as needed. Results showed that Nedd4L cKO in IEC (not hepatocytes or HSC) significantly promoted LF, accompanied by marked reductions in the abundances of gut Lactobacillus , Desulfovibrio , Tyzzerella , Alistipes , Bacteroides and Colidexteribacter , and significantly decreased serum IFN1. Without the CCL4 challenge, Nedd4L cKO in IEC also reduced gut Lactobacillus , Bacteroides , Alistipes and serum IFN1. In mice with Nedd4L cKO in IEC, intragastric administration of Lactobacillus (not Bacteroides ) significantly attenuated LF, accompanied by significantly increased gut Lactobacillus , Bacteroides , Alloprevotella , Faecalibaculum and serum IFN1 level; however, Lactobacillus-mediated LF alleviation was antagonized upon deletion of the organismal IFN1 receptor. Finally, the LF degree could still be relieved by exogenous IFNα even when NEDD4L signaling in IEC was blocked. Overall, this study demonstrates that curbing CCL4-induced LF in C57BL/6J mice by endogenous IFN1 signaling requires intestinal NEDD4L signaling, which maintains the abundance of the gut genera Lactobacillus and thus facilitates endogenous IFN1 production.

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

Scalable upcycling of medical plastic waste using metals-doped hierarchically porous biocarbon for tunable fuel-grade hydrocarbons or H2-enriched fuel gas - Guanyu Zhang; Qing Cheng; Ge Kong; Yuan Jiang; Xin Zhang; Tianqi Cao; Jingyou Bi; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Fuel, 2026)

Achieving 17.65% efficiency in organic solar cells by neutral linker engineering in dimerized small-molecule acceptors - Jianan Niu; Xue Zhou; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Cheng Sun; Tan Wang; Mingliang Sun; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2026)

Understanding the spatial heterogeneity of black carbon variation drivers in China: Views from explainable machine learning - Huang Zheng; Weiwei Chen; Xiaohui Bi; Nan Chen; Cheng Wu; Mingming Zheng; Shaofei Kong (Atmospheric Research, 2026)

Determining the Biological Zero and Effective Accumulated Temperature for Gonadal Development in Diploid and Tetraploid Pacific Oysters, Crassostrea gigas - Geng Cheng; Jianmin Zhou; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Qi Li (Journal of Ocean University of China, 2026)

Isolation and identification of a centromeric tandemly repeated DNA sequence in Saccharina japonica - Yi-Yan Cai; Cheng Zhang; Si-Qi Chen; Zhi Li; Zhi-Gang Zhou; Yan-Hui Bi (Algal Research, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Dissolved and particulate phosphorus turnover in a river dominated marginal sea traced by cosmogenic 32P and 33P - Cheng Xu; Bin Yang; Jinlong Wang; Sheng Zeng; QianQian Bi; Jinzhou Du (Water Research, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Capture-and-degrade strategy using defect-engineered MOF fibers for efficient diclofenac removal from water - Yanxin Gao; Longying Duan; Ting Cheng; Lisi Zheng; Yihao Dou; Guocheng Huang; Jinhong Bi (Chemical Engineering Journal, 2026)

Multiple Regression and Path Analysis of Morphological, Weight, and Fecundity Traits of Diploid and Tetraploid Pacific Oyster, Crassostrea gigas - Geng Cheng; Hong Hu; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

Projection-based molecular feature maps for CNN-driven nephrotoxicity prediction - Muhammad Zafar Irshad Khan; Jia-Nan Ren; Hong-Yu-Xiang Ye; Cheng Cao; Xiao-Bi Liu; Jian-Zhong Chen (Archives of Toxicology, 2026)

Mechanism by Which Exogenous GABA Enhances the Tolerance of Potatoes to Low-Potassium Conditions - Fengjuan Wang; Ruijie Zuo; Shang Shi; Junrong Cheng; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (American Journal of Potato Research, 2026)

Analysis of the efficient and stable organic matter removal performance and microbial community in a two-stage A/O-MBBR pilot-scale system - Shuo Li; Xiaowan Dong; Juntao Cheng; Fangshu Wang; Liyan Wang; Xifeng Zhao; Shuoyang Wang; Guosheng Wang; Qingyang Bi; Reng Zhang; Dong Chen (Journal of Water Process Engineering, 2026)

Effectiveness of a novel magnetic negative stiffness eddy-current damper for multi-mode vibration control of stay cables: Experimental and numerical investigations - Zhipeng Cheng; Ruisheng Ma; Zhihao Wang; Xiuli Du; Kaiming Bi (Engineering Structures, 2026)

Significantly enhanced effects of heavy metals on the toxicity, bioconcentration and biomagnification under combined exposure - Qian Cheng; Jin Zhang; Bi-ya Dai; Xin-yue Wang; Guang-zhen Ji; Yuan-fan Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Sources of asarum allelopathic exudates and mitigating effects of rhizosphere fungi - Xinhua Bi; Fuqi Wang; Haitao Cheng; Di Yuan; Shiying Li; Yingni Pan; Xiaoqiu Liu; Dongmei Wang (European Journal of Plant Pathology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Enhancing anaerobic methane production from corn straw: Promoting lignocellulosic biomass biodegradation via aeration in liquid fraction of digestate for green and efficient pretreatment - Bi-Long Chen; Ting-Ting Zhang; Aqsa Arooj; Cheng Xu; Jia-Cheng E. Yang; Mika Sillanpää; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Multi-omics profiling delineates reheating-modality-driven flavor divergence in Yuxiang shredded pork - Xuan Wang; Shaoran Shi; Xiaomeng Wu; Shuang Bi; Fan Yang; Xiuli Du; Youyou Cheng; Jingguang Li; Yunfeng Zhao; Dawei Chen (Food Chemistry, 2025)

Water resistance and hydration mechanism of phosphogypsum cemented paste backfill under composite curing agent modification - Shulong Liu; Yiming Wang; Aixiang Wu; Zhuen Ruan; Cheng Bi; Yuanchang Li (Environmental Research, 2025)

Thermal resilience in pilot-scale anoxic/oxic moving-bed biofilm reactor enables robust removal of pharmaceuticals and antibiotic resistance genes - Xiaowan Dong; Jie Lan; Yuan Gao; Dong Chen; Kailing Pan; Fangshu Wang; Xiaolin Zhou; Xueqing Shi; Lihua Cheng; Xuejun Bi (Bioresource Technology, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Migratory birds as a vector for viral interregional transmission: genetic diversity of avian influenza virus in bird feces from the Tianshan wetland ecosystems - Fengze Yun; Haiyang Wang; Kamila Aisaiti; Tong Wu; Cheng Zhang; Fengnian Chen; Yuhai Bi; Zhenghai Ma (European Journal of Wildlife Research, 2025)

Comparison of Lycium barbarum and Chenopodium glaucum litter decomposition reveals differential impacts on fusarium abundance and microbial community structure under field conditions - Chuanji Zhang; Zhenyu Cheng; Xiaoqi He; Meiyun Pu; Junjie Li; Ziyu Liu; Xiaomin Wang; Yurong Bi; Liguang Wang; Xiaofan Na (Applied Soil Ecology, 2025)

A highly sensitive magnetic separation-assisted electrochemical sensor for detection of m6A-microRNA-17–5p based on rolling circle amplification and N3-kethoxal labeling strategy at LIG electrodes - Xi Cheng; Jingyi Guo; Huiyan Cao; Haiyue Bi; Shouquan Dong; Hongling Wang; Xiaocheng Weng; Fang Wang (Analytica Chimica Acta, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Miocene N-MORB- and OIB-type diabase dikes in the western Yarlung Tsangpo suture zone, southern Tibet: Insights into the Indian slab tearing and asthenosphere–lithosphere interaction - Jianbo Cheng; Yalin Li; Xianshu Dong; Siqi Xiao; Shuai Li; Wenjun Bi; Rui Zhou (Lithos, 2025)

Distribution, ozone formation potential, and health risk assessments of VOCs in automotive seat cushion leather during finishing process - Zhaohui Yang; Chuanhui Mu; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Hazardous Materials, 2025)

Influences of hydrological and agricultural conditions on selenium distribution in groundwater: A case study in Sanjiang plain, Northeast China - Yajie Pang; Xuxue Cheng; Jin He; Weipo Liu; Xue Niu; Erping Bi (Journal of Contaminant Hydrology, 2025)

Circ-379-miR-3050-DNAH3/RNF8 axis modulates wing development in Aphis citricidus - Yu-Jing Liu; Jin-Ming Lu; Xiu-Cheng Xie; Qin-Qin Xu; Bi-Yue Ding; Jin-Jun Wang; Feng Shang (Insect Biochemistry and Molecular Biology, 2025)

Wet deposition fluxes of cosmogenic 32P, 33P and its utility in tracing air mass mixing in coast of east China sea - Cheng Xu; Sheng Zeng; QianQian Bi; Gi-Hoon Hong; Jinzhou Du (Atmospheric Environment, 2025)

Increase in CO2 concentration reduces the competitiveness of 2-methylisoborneol-producing cyanobacteria: evidence from Pseudanabaena - Pengfei Qiu; Wujuan Mi; Gaofei Song; Fengfeng Cheng; Yonghong Bi (Journal of Oceanology and Limnology, 2025)

lewis-base-triggered dehydrofluorination and interfacial synergy in composite electrolytes toward high-performance all-solid-state batteries - Tong Duan; Shuyu Bi; Jie Liu; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2025)

Sustainable and versatile bioplastics toward large-scale industrialization - Chunyu Wang; Yingying He; Yuan Wei; Yong Ye; Hongfu Bi; Cheng Zhang; Jie Ao; Tianning Yang; Feng Chen; Yangyang Qian; Yongjun Xu; Gang Chen (Chemical Engineering Journal, 2025)

Atrazine-induced hippocampal neurotoxicity: Involvement of Drp1-mediated mitochondrial fission - Jingran Yang; Ling Qi; Cheng Zhang; Ruirui Ding; Haoran Bi; Peng Li; Zhipeng Qi; Qiao Niu; Weiyi Song; Jianan Li (Chemico-Biological Interactions, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Seasonal Variations and Potential Sources of Black Carbon at a Mountain Site in the Central Yunnan Plateau, China - Yanli Wang; Yan Cheng; Song Liu; Feng Xiang; Limei Bi; Qiaoli Wu; Xuan Tian; Shiting Chen; Zechen Gu; Feng Wu (Aerosol Science and Engineering, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

The GLI3 may be involved in the damage process of Eimeria tenella to chicken cecal tissue - Wanjiang Xiang; Ying Chen; Ye He; Yongmei Yu; Ping Li; Bi Wang; Zhentao Cheng (Veterinary Parasitology, 2025)

Associations of non-essential metal mixture with biological aging and the mediating role of inflammation in Chinese older adults - Yan Zhang; Yuan Wang; Xuqiu Cheng; Ziwei Tian; Yuantao Zhang; Wenyuan Liu; Xianglong Liu; Bing Hu; Fangbiao Tao; Anna Bi; Jun Wang; Linsheng Yang (Environmental Pollution, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Bayesian-based analysis of sequence activity characteristics in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2025)

The Trp-574-Leu mutations together with enhanced metabolism contribute to cross-resistance to ALS inhibiting herbicides in Fimbristylis littoralis - Yueyue Shi; Zhiwen Wu; Rui Cheng; Lilei Zhang; Xiaoxiao Guo; Xuefeng Li; Yaling Bi (Pesticide Biochemistry and Physiology, 2025)

Revealing the key organelle in the pathophysiology and clinical applications of animal toxins: Mitochondria - Linfeng Wang; Jiahao Liu; Sheng Zhou; Jiaqi Sun; Meiling Liu; Jianqi Zhao; Lixia Cheng; Zejing Wen; Xiaowen Bi; Chunhong Huang (Toxicon, 2025)

Total resource circulation in chemical mechanical polishing wastewater treatment from semiconductor manufacturing industry: A review - Bi-Cheng Chang; Hsing-Jung Ho; Atsushi Iizuka (Journal of Water Process Engineering, 2025)

Study on the effect of multistage A/O-MBBR pilot system on urban sewage treatment: Removal contribution and microbial community changes - Qingyang Bi; Xiaowan Dong; Jicheng Duan; Fangshu Wang; Shixin Yu; Lihua Cheng; Xuejun Bi; Dong Chen (Journal of Environmental Chemical Engineering, 2025)

The effect of oil types on the droplet shape and rheology of emulsion gels stabilized with camellia saponin - Shengnan Li; Panpan Li; Jing Wang; Yanju Lu; Yuxiang Chen; Zhendong Zhao; Jianxin Jiang; Xian Cheng; Liangwu Bi (Fuel, 2025)

Crosslinked protein-polysaccharide nanocomposite coating for pork preservation: Impact on physicochemical properties and microbial structure - Xianmin Qin; Linqin Chen; Jingjing Zhao; Wenxin Zhang; Haimiao Tian; Shenghui Bi; Guofeng Jin; Ying Zhou; Qiujin Zhu; Yuxin Cheng; Yuanyuan Liu (Food Chemistry, 2025)

An in-situ adjustable arrayed magnetic negative stiffness device: Analytical modelling, experimental testing, and parametric study - Zhipeng Cheng; Ruisheng Ma; Kaiming Bi; Zhihao Wang; Xiuli Du (Engineering Structures, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

High-strength, high-toughness, and high-barrier composite films based on bionic multi-scale fiber reinforcement and organic–inorganic interface hybridization for flexible food packaging - Cheng Zhang; Hongfu Bi; Yuan Wei; Yang Zhou; Chunyu Wang; Yingying He; Jie Ao; Shimin Kang; Gang Chen (Chemical Engineering Journal, 2025)

Optimization of Microsatellite Multiplex PCRs for Triploidy Verification and Genetic Diversity Assessment in the Pacific Oyster, Crassostrea gigas - Huilin Zheng; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Wenlong Bi; Hong Hu; Qi Li (Marine Biotechnology, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Comparative analysis of chromatin accessibility in porcine oocytes from follicles of different sizes - Yazhuo Cheng; Jingyu Li; Jiyong Shang; Xilong Jia; Yeling Bi; Jiaxu Gu; Nan Jiang; Yanjun Huan; Youwei Li; Mingju Sun (Research in Veterinary Science, 2025)

Acetaminophen overdose inhibits steroidogenic acute regulatory protein expression by reducing AKT-mediated SP1 expression in human granulosa-lutein cells - Jung-Chien Cheng; Qian Zhang; Lingling Zhang; Beibei Bi; Hailong Wang; Lanlan Fang; Hsun-Ming Chang; Ying-Pu Sun (Reproductive Toxicology, 2025)

Optimized dense fibril network by ternary strategy to improve charge transport and realize efficient organic solar cells - Chuanlong Cui; Cheng Sun; Yuyi Bi; Shuyu Yao; Yuchang Zhao; Jianxiao Wang; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2025)

Dimerized small-molecule acceptors with electron withdrawing linker for efficient organic solar cells - Jianan Niu; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Shuguang Wen; Cheng Sun; Mingliang Sun; Xichang Bao (Chemical Engineering Journal, 2025)

Clustering of Earthquake Sequence and Its Effect on b Value in North China - Jinmeng Bi; Cheng Song; Yong Ma (Pure and Applied Geophysics, 2025)

MMP13 as an effective target of an active trifluoromethyl quinazoline compound against osteosarcoma - Chang-hua Zhou; Ting Zhang; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Bi-xue Xu; Heng Luo; Xiao-bin Tian (Toxicology and Applied Pharmacology, 2025)

A novel aggregation-induced emission-featured hyperbranched poly(amido amine)s stabilized copper nanoclusters‑cerium (III) sensor for detection of thiol flavor compounds in processed meat - Xiaoxian Tian; Liang Li; Xiaochun Zheng; Bai-Tong Liu; Li Chen; Zhenyu Wang; Yongzhao Bi; Guangchun Song; Shaobo Li; Qingye Meng; Cheng Li; Dequan Zhang (Food Chemistry, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

IsoVISoR: Towards 3D Mesoscale Brain Mapping of Large Mammals at Isotropic Sub-micron Resolution - Chao-Yu Yang; Yan Shen; Xiaoyang Qi; Lufeng Ding; Yanyang Xiao; Qingyuan Zhu; Hao Wang; Cheng Xu; Pak-Ming Lau; Pengcheng Zhou; Fang Xu; Guo-Qiang Bi (Neuroscience Bulletin, 2025)

Mechanism of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid toxicity in Carassius auratus through the microbiota–gut–brain axis - Xue Jiao; Faye Zhang; Lei Guo; Zheng-Yao Guo; Qiu-Shuang Fu; Cheng-Cheng Bi; Xian-Wei Hou; Ning Wang; Jing-Xiang Zhou; Yue-Hong Li (Aquaculture, 2025)

Simulation study on the effect of temperature on hydrogen production performance of alkaline electrolytic water - Xiaobing Bi; Gan Wang; Daan Cui; Xinyi Qu; Shuaishuai Shi; Dong Yu; Mojie Cheng; Yulong Ji (Fuel, 2025)

Generation of unpaired electrons to promote electron transfer at the cathode of room-temperature sodium sulfur batteries - Chen Huang; Jing Yu; Yao-Jie Lei; Oleg Usoltsev; Li Gong; Zhibiao Cui; Junshan Li; Canhuang Li; Bingfei Nan; Xuan Lu; Ren He; Xuede Qi; et al. (Chemical Engineering Journal, 2025)

PLCFishMOT: multiple fish fry tracking utilizing particle filtering and attention mechanism - Huachao Tan; Yuan Cheng; Dan Liu; Guihong Yuan; Yanbo Jiang; Hongyong Gao; Hai Bi (Aquaculture International, 2025)

Potential for synergism of sequential UV-NaClO disinfection on ARGs removal in municipal sewage: Effectiveness, kinetics, and mechanisms - Xiaohan Wei; Jie Wang; Tengfei Hu; Zihui Liu; Aili Gao; Dong Jiang; Lihua Cheng; Shujuan Huang; Xiaolin Zhou; Xuejun Bi (Journal of Environmental Chemical Engineering, 2024)

Fine mapping and functional validation of the candidate gene BhGA2ox3 for fruit pedicel length in wax gourd (Benincasa hispida) - Yan Deng; Peng Wang; Wenhui Bai; Zhihao Chen; Zhikui Cheng; Liwen Su; Xianglei Chen; Yeshun Bi; Rongjin Feng; Zhengguo Liu (Theoretical and Applied Genetics, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Experimental species removal reveals species contributions to positive pollinator‐mediated reproductive interactions - Cheng Bi; Øystein H. Opedal; Ting Yang; Erliang Gao; Zhigang Zhao (Ecology, 2024)
Pollinator‐mediated reproductive interactions among co‐flowering plant species provide a canonical example of how biotic factors may contribute to species coexistence, yet we lack understanding of the exact mechanisms. Flowering‐dominant and unusually attractive “magnet species” with disproportionate contributions to pollination may play key roles in such reproductive interactions, but their relative roles within the same community have rarely been assessed. We experimentally removed either a flowering‐dominant or a highly attractive magnet species and compared effects on visitation frequency, pollinator richness, and seed set of co‐flowering plants. Removal of either the flowering‐dominant species or the magnet species reduced community‐level pollinator visitation. Removal of the magnet species had the most consistent effect, including reduced pollinator visitation and richness, and reduced seed set of most co‐flowering plants. These results suggest that the magnet species, which interacts with a wider range of pollinator species than does the dominant species, promotes the visitation and reproductive fitness of most other species. Removal of the flowering‐dominant species affected only certain species, perhaps because these plants had floral traits similar to the dominant species. Our results highlight the role of attractive magnet species within a community in structuring reproductive interactions and identify potential mechanisms involved in coexistence facilitated by reproductive interactions.

The relationship between maternal environmental temperature exposure and preterm birth: A Risk prediction based on machine learning - Yuxiao Wang; Xing Bi; Yang Cheng; Yingjie Du; Ling Feng; Shaoshuai Wang (Sustainable Cities and Society, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Predictive modeling of patulin accumulation in apple lesions infected by Penicillium expansum using machine learning - Xiaoyan Cheng; Rongxia Li; Pengdong Xie; Xuexue Wang; Lirong Yu; Ruofei Wu; Huali Xue; Yang Bi (Postharvest Biology and Technology, 2024)

Portulaca oleracea (L.) essential oil inhibits Pestalotiopsis neglecta and controls black spot needle blight in Pinus sylvestris var. mongolica (Litv.) - Weihu Ma; Cheng Chen; Qiuer Sa; Yundi Zhang; Jingyu Ji; Bing Bi; Wenzhuo Sun; Jie Zhang; Guocai Zhang (Physiological and Molecular Plant Pathology, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Efficient PPCPs removal from wastewaters via a novel A/O-MBBR system: Transition towards circular economy in the water sector - Xiaowan Dong; Fangshu Wang; Shixin Yu; Jie Lan; Xing Fan; Xiaolin Zhou; Wei Wei; Guo Li; Lihua Cheng; Xuejun Bi; Ruibo Hu; Dong Chen (Journal of Environmental Management, 2024)

Recent advances in photoluminescent fluorescent probe technology for food flavor compounds analysis - Xiaoxian Tian; Xiaochun Zheng; Li Chen; Zhenyu Wang; Bai-Tong Liu; Yongzhao Bi; Liang Li; Haonan Shi; Shaobo Li; Cheng Li; Dequan Zhang (Food Chemistry, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A CNNGRU-MHA method for ship trajectory prediction based on marine fusion data - Jinqiang Bi; Miao Gao; Kexin Bao; Wenjia Zhang; Xuefeng Zhang; Hongen Cheng (Ocean Engineering, 2024)

A novel dual swirling air curtain dust-control system: Design and similar experiment - Cheng Shen; Dong Wang; Jing Zhang; Qiuping Bi (Journal of Environmental Chemical Engineering, 2024)

Degradation of Diclofenac in Water Using S2O82−/Fe2O3-zeolite Catalyst Synergistic with Ozone - Yuanbo Song; Qingsong Xu; Mengyu Jin; Jiaqi Wang; Xiaoxia Wang; Cheng Hou; Zhenqi Wang; Dongsu Bi; Zheng Shen; Yalei Zhang (Water, Air, & Soil Pollution, 2024)

Multimodal quantitative segmental analysis of seismicity of the Zhangjiakou-Bohai tectonic belt (North China) - Jinmeng Bi; Cheng Song; Fuyang Cao; Yong Ma (Journal of Seismology, 2024)

Identification ATP5F1D as a Biomarker Linked to Diagnosis, Prognosis, and Immune Infiltration in Endometrial Cancer Based on Data-Independent Acquisition (DIA) Analysis - Yuemei Cheng; Xiaolei Liang; Xuehan Bi; Chang Liu; Yongxiu Yang (Biochemical Genetics, 2024)

Correction: Experimental grazer exclusion increases pollination reliability and influences pollinator-mediated plant-plant interactions in Tibetan alpine meadows - Cheng Bi; Øystein H. Opedal; Ting Yang; Lili Yang; Erliang Gao; Meng Hou; Zhigang Zhao (Alpine Botany, 2024)

Alleviation of RO membrane fouling in wastewater reclamation plants using an enhanced acid-base chemical cleaning method - Li Zihao; Jinlong Wang; Lihua Cheng; Qiang Yang; Peizhuo Li; Xiaowan Dong; Boyan Xu; Mei Zhi; Anni Hao; How yong Ng; Xuejun Bi (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Intensive coagulation of secondary effluent to mitigate reverse osmosis membrane fouling at low temperatures: Strategies of pre-oxidation and coagulant aids addition - Qiang Yang; Xiaohan Wei; Tengfei Hu; Jie Wang; Peizhuo Li; Aili Gao; Jinlong Wang; Lihua Cheng; Shujuan Huang; Xuejun Bi (Journal of Water Process Engineering, 2024)

The monokaryotic filamentous fungus Ustilago sp. HFJ311 promotes plant growth and reduces Cd accumulation by enhancing Fe transportation and auxin biosynthesis - Shengwang Wang; Xiaofan Na; Meiyun Pu; Yanfang Song; Junjie Li; Kaile Li; Zhenyu Cheng; Xiaoqi He; Chuanji Zhang; Cuifang Liang; Xiaomin Wang; Yurong Bi (Journal of Hazardous Materials, 2024)

Temporal accumulation and lag effects of precipitation on carbon fluxes in terrestrial ecosystems across semi-arid regions in China - Haixing Gong; Guoyin Wang; Chenqing Fan; Xianwang Zhuo; Lina Sha; Zexing Kuang; Jianrong Bi; Tiantao Cheng (Agricultural and Forest Meteorology, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

A robust and low-cost blended-fiber-based evaporator with high efficiency for solar desalination - Qianqian Liu; Xiangjun Liu; Ge Chen; Pei Feng; Yucheng Xiong; Meng An; Cheng Shao; Xiongfei Zhu; Renzong Wang; Jianshi Sun; Jisheng Sun; Chunfang Guo; et al. (Desalination, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Exogenous ethanol induces cell giantism accompanied by enhanced accumulation of lipid and carbohydrates in Chlorella sorokiniana - Rediat Abate; Yonghong Bi; Gaofei Song; Wujuan Mi; Fengfeng Cheng; Yuxuan Zhu (Journal of Applied Phycology, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Determining the optimal thin layer height for single-station ionospheric modeling and its influence on the estimation of DCB - Hui Xi; Hu Jiang; Jiachun An; Na Cheng; Tianyang Bai; Jingxue Bi (GPS Solutions, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

Water quality characteristics and ecological risk evaluation of a landscaped river replenished by three reclaimed water sources in Qingdao, China - Yanan Cai; Yunze Bi; Bowen Tian; Lihua Cheng; Shuhui Zhou; Quanyong Qi (Environmental Science and Pollution Research, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Editorial: Deep learning for marine science - Haiyong Zheng; Hongsheng Bi; Xuemin Cheng; Mark C. Benfield (Frontiers in Marine Science, 2024)

Advances in biotin biosynthesis and biotechnological production in microorganisms - Jia-Run Zhao; Si-Qi Zuo; Feng Xiao; Feng-Zhu Guo; Lu-Yi Chen; Ke Bi; Dong-Yuan Cheng; Zhi-Nan Xu (World Journal of Microbiology and Biotechnology, 2024)

A rice GT61 glycosyltransferase possesses dual activities mediating 2-O-xylosyl and 2-O-arabinosyl substitutions of xylan - Ruiqin Zhong; Dayong Zhou; Dennis R. Phillips; Earle R. Adams; Lirong Chen; John P. Rose; Bi-Cheng Wang; Zheng-Hua Ye (Planta, 2024)

Experimental grazer exclusion increases pollination reliability and influences pollinator-mediated plant-plant interactions in tibetan alpine meadows - Cheng Bi; Øystein H. Opedal; Ting Yang; Lili Yang; Erliang Gao; Meng Hou; Zhigang Zhao (Alpine Botany, 2024)

Artificial Intelligence in Ship Trajectory Prediction - Jinqiang Bi; Hongen Cheng; Wenjia Zhang; Kexin Bao; Peiren Wang (Journal of Marine Science and Engineering, 2024)
Maritime traffic is increasing more and more, creating more complex navigation environments for ships. Ship trajectory prediction based on historical AIS data is a vital method of reducing navigation risks and enhancing the efficiency of maritime traffic control. At present, employing machine learning or deep learning techniques to construct predictive models based on AIS data has become a focal point in ship trajectory prediction research. This paper systematically evaluates various trajectory prediction methods, spanning classical machine learning approaches and emerging deep learning techniques, to uncover their respective merits and drawbacks. In this work, a variety of studies were investigated that applied different algorithms in ship trajectory prediction, including regression models (RMs), artificial neural networks (ANNs), Kalman filtering (KF), and random forests (RFs) in machine learning, along with deep learning such as convolutional neural networks (CNNs), recurrent neural networks (RNNs), long short-term memory (LSTM), gate recurrent unit (GRU) networks, and sequence-to-sequence (Seq2seq) networks. The performance of predictive models based on different algorithms in trajectory prediction tasks was graded and analyzed. Among the existing studies, deep learning methods exhibit significant performance and considerable potential application value for maritime traffic systems, which can be assessed by future work on ship trajectory prediction research.

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Characterization and stability of low-oil emulsion gels with newly shaped droplets stabilized by camellia saponin and k-carrageenan - Shengnan Li; Panpan Li; Jing Wang; Yanju Lu; Yuxiang Chen; Zhendong Zhao; Jianxin Jiang; Xian Cheng; Liangwu Bi (Food Hydrocolloids, 2024)

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Bronchoalveolar Lavage Fluid Microbiota is Associated with the Diagnosis and Prognosis Evaluation of Lung Cancer - Chen Cheng; Zhifeng Wang; Chao Ding; Pingli Liu; Xiaoqiang Xu; Yan Li; Yi Yan; Xiaocong Yin; Bi Chen; Bing Gu (Phenomics, 2024)

Correction to: Melatonin ameliorates osteoarthritis rat cartilage injury by inhibiting matrix metalloproteinases and JAK2/STAT3 signaling pathway - Zhongyuan Zhao; Benjun Bi; Gong Cheng; Yuchi Zhao; Hao Wu; Mingdi Zheng; Zhilin Cao (Inflammopharmacology, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Measuring ecosystem services and ecological sensitivity for comprehensive conservation in Giant Panda National Park - Cheng Li; Rong Hou; Ziqiang Bao; Wei Wu; Jacob R. Owens; Wenlei Bi; Qiang Xu; XiaoDong Gu; Zuofu Xiang; Dunwu Qi (Conservation Biology, 2024)
China announced the development of its first 5 national parks in 2021, the primary objective of which is to conserve the natural state and integrity of natural ecosystems. As such, ecosystem services and biodiversity levels are crucial assessment factors for the parks. For Giant Panda National Park (GPNP), we evaluated ecological sensitivity based on water and soil erosion and rocky desertification; ecosystem services based on headwater conservation, soil and water conservation, and biodiversity conservation; and presence of giant panda ( Ailuropoda melanoleuca ) and sympatric species (e.g., takin [ Budorcas taxicolor ], Asiatic black bear [ Ursus thibetanus ]) habitat suitability derived from niche modeling to identify the ecosystem status and assess ecological problems within the park. From our results, we proposed ecologically critical areas to target to meet the park's goals. The suitable habitat for pandas and sympatric species encompassed 62.98% of the park and occurred mainly in the Minshan Mountains. One quarter of the total area (25.67%) contained areas important for ecosystem services. Ecologically sensitive and extremely sensitive areas covered 88.78% of the park and were distributed mainly in Qionglaishan and Minshan Mountains. This coverage indicated that there was much habitat for pandas and sympatric species but that the ecosystems in GPNP are vulnerable. Therefore, ecologically critical areas encompassed all suitable habitats for all the species examined and areas important and extremely important to ecosystem service provision,ecologically sensitive and extremely sensitive areas, encompassed 15.17% of panda habitat, accounted for 16.37% of the GPNP area, and were distributed mainly in the Minshan Mountains. Our results indicated where conservation efforts should be focused in the park and that by identifying ecologically critical areas managers can provide targeted protection for wildlife habitat and ecosystems and effectively and efficiently protect the composite ecosystem. Additionally, our methods can be used to inform development of new national parks.

Cu2O/WO3 S-scheme heterojunctions for photocatalytic degradation of levofloxacin based on coordination activation - Qi Chen; Ling Hu; Yingzhang Shi; Cheng Liu; Yidong Hou; Jinhong Bi; Jimmy C. Yu; Ling Wu (Chemosphere, 2024)

Numerical simulations of wave sheltering in coastal waters with submerged tensioned viscoelastic sheets using smoothed particle hydrodynamics - Xiaodong Liu; Adrian Wing-Keung Law; Dharma K.K. Sree; Cheng Bi (Ocean Engineering, 2024)

Laboratory and field characterization of preferential flow under consideration of geometric fracture features in a karst region in southwest China - Ning Guan; Jinhua Cheng; Huaxing Bi; Xueqi Shi (Journal of Hydrology, 2024)

A dolomite-based record of seawater calcium isotope composition over the Neogene - Xiao-Feng Liu; Xiao-Ming Liu; Shikui Zhai; Zhaofeng Zhang; Dongjie Bi; Xi-Kai Wang; Cheng Cao; Xinyu Liu (Geochimica et Cosmochimica Acta, 2024)

Automated zooplankton size measurement using deep learning: Overcoming the limitations of traditional methods - Wenjie Zhang; Hongsheng Bi; Duansheng Wang; Xuemin Cheng; Zhonghua Cai; Kezhen Ying (Frontiers in Marine Science, 2024)
Zooplankton size is a crucial indicator in marine ecosystems, reflecting demographic structure, species diversity and trophic status. Traditional methods for measuring zooplankton size, which involve direct sampling and microscopic analysis, are laborious and time-consuming. In situ imaging systems are useful sampling tools; however, the variation in angles, orientations, and image qualities presented considerable challenges to early machine learning models tasked with measuring sizes.. Our study introduces a novel, efficient, and precise deep learning-based method for zooplankton size measurement. This method employs a deep residual network with an adaptation: replacing the fully connected layer with a convolutional layer. This modification allows for the generation of an accurate predictive heat map for size determination. We validated this automated approach against manual sizing using ImageJ, employing in-situ images from the PlanktonScope. The focus was on three zooplankton groups: copepods, appendicularians, and shrimps. An analysis was conducted on 200 individuals from each of the three groups. Our automated method's performance was closely aligned with the manual process, demonstrating a minimal average discrepancy of just 1.84%. This significant advancement presents a rapid and reliable tool for zooplankton size measurement. By enhancing the capacity for immediate and informed ecosystem-based management decisions, our deep learning-based method addresses previous challenges and opens new avenues for research and monitoring in zooplankton.

Performance and mechanism of sequential UV-NaClO disinfection: Inactivation and reactivation of antibiotic-resistant bacteria, disinfection byproduct formation and microbial community variation - Lihua Cheng; Xiaohan Wei; Aili Gao; Lin Zhou; Xueqing Shi; Xiaolin Zhou; Xuejun Bi; Tang Yang; Shujuan Huang (Journal of Water Process Engineering, 2024)

Comprehensive analysis of effects of magnetic nanoparticles on aerobic granulation and microbial community composition: From the perspective of acyl-homoserine lactones mediated communication - Kailing Pan; Yuxuan Wei; Chen Qiu; Hongyu Li; Ling Wang; Lihua Cheng; Xuejun Bi (Bioresource Technology, 2024)

The role of corneal endothelium in macular corneal dystrophy development and recurrence - Bi-Ning Zhang; Benxiang Qi; Chunxiao Dong; Bin Zhang; Jun Cheng; Xin Wang; Suxia Li; Xiaoyun Zhuang; Shijiu Chen; Haoyun Duan; Dewei Li; Sujie Zhu; et al. (Science China Life Sciences, 2024)

Long-term effects of thiosulfate on the competition between sulfur-mediated bacteria and glycogen accumulating organisms in sulfate-rich carbon-deficient wastewater - Lichang Zhou; Zhaoling Li; Boyi Cheng; Jinqi Jiang; Xinqi Bi; Zongping Wang; Guanghao Chen; Gang Guo (Environmental Research, 2024)

Exploring ANFIS application based on actual data from wastewater treatment plant for predicting effluent removal quality of selected major pollutants - Liang Qiao; Pei Yang; Qi Leng; Liujie Xu; Yanxin Bi; Jinzhen Xu; Zhe Wang; Jianye Liu; Wanxin Yin; Luyan Zhang; Feihong Wang; Ye Yuan; et al. (Journal of Water Process Engineering, 2023)

Ecological implications of plant clonality - Sergio R. Roiloa; Wei Xue; Bi-Cheng Dong; Fei-Hai Yu (Flora, 2023)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Uniform deposition of metal-organic coordination networks on BiVO4 through chemical bonding for efficient solar water splitting - Xiang Cheng; Libin Ji; Yingying Bi; Wei Wang; Shutao Gao; Huiliang Li; Ningzhao Shang; Wei Gao; Chenchen Feng; Chun Wang (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the mechanism of the effect of perfluorocaproic acid exposure on brain injury in Carassius auratus - Xue Jiao; Zheng yao Guo; Jia Sun; Cheng Bi; Ai-dong Qian; Yue-hong Li (Aquatic Toxicology, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Toward efficient deep learning system for in-situ plankton image recognition - Junbai Yue; Zhenshuai Chen; Yupu Long; Kaichang Cheng; Hongsheng Bi; Xuemin Cheng (Frontiers in Marine Science, 2023)
Plankton is critical for the structure and function of marine ecosystems. In the past three decades, various underwater imaging systems have been developed to collect in-situ plankton images and image processing has been a major bottleneck that hinders the deployment of plankton imaging systems. In recent years, deep learning methods have greatly enhanced our ability of processing in-situ plankton images, but high-computational demands and longtime consumption still remain problematic. In this study, we used knowledge distillation as a framework for model compression and improved computing efficiency while maintaining original high accuracy. A novel inter-class similarity distillation algorithm based on feature prototypes was proposed and enabled the student network (small scale) to acquire excellent ability for plankton recognition after being guided by the teacher network (large scale). To identify the suitable teacher network, we compared emerging Transformer neural networks and convolution neural networks (CNNs), and the best performing deep learning model, Swin-B, was selected. Utilizing the proposed knowledge distillation algorithm, the feature extraction ability of Swin-B was transferred to five more lightweight networks, and the results had been evaluated in taxonomic dataset of in-situ plankton images. Subsequently, the chosen lightweight model and the Bilateral–Sobel edge enhancement were tested to process in-situ images with high level of noises captured from coastal waters of Guangdong, China and achieved an overall recall rate of 91.73%. Our work contributes to effective deep learning models and facilitates the deployment of underwater plankton imaging systems by promoting both accuracy and speed in recognition of plankton targets.

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Role of Mutations of Mitochondrial Aminoacyl-tRNA Synthetases Genes on Epileptogenesis - Ling-yue Kong; Yi-ze Wu; Run-qi Cheng; Pei-han Wang; Bi-wen Peng (Molecular Neurobiology, 2023)

Temporal and spatial changes of water quality in intensively developed urban rivers and water environment improvement: a case study of the Longgang River in Shenzhen, China - Xupo Zhang; Gong Cheng; Shengjun Xu; Yeliang Bi; Cancan Jiang; Shuanglong Ma; Dongsheng Wang; Xuliang Zhuang (Environmental Science and Pollution Research, 2023)

Safety assessment of organic micropollutants in reclaimed water: Chemical analyses, ecological risk assessments, and in vivo endocrine-disrupting studies - Fei Zhao; Yinfei Hao; Qianru Xu; Zhineng Hao; Xinhui Li; Lihua Cheng; Dong Chen; Xueqing Shi; Yihua Xiao; Penghao Wei; Xuejun Bi (Science of The Total Environment, 2023)

Potassium assisted pyrolysis of Chinese Baijiu distillers' grains to prepare biochar as controlled-release K fertilizer - Jiali Cheng; Jiaming Zhang; Xiao Xiao; Yue Yuan; Xuepin Liao; Bi Shi; Suyi Zhang (Science of The Total Environment, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Quantifying seasonal ground deformation in Taiyuan basin, China, by Sentinel-1 InSAR time series analysis - Wei Tang; Xiangjun Zhao; Gang Bi; Mingjie Chen; Siyu Cheng; Mingsheng Liao; Wenjun Yu (Journal of Hydrology, 2023)

Preparation of P-doped biochar and its high-efficient removal of sulfamethoxazole from water: Adsorption mechanism, fixed-bed column and DFT study - Yizhen Cheng; Jingrui Yang; Jimin Shen; Pengwei Yan; Shan Liu; Jing Kang; Lanbo Bi; Binyuan Wang; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2023)

Chemoreceptors from the commensal gut Roseburia rectibacter bind to mucin and trigger chemotaxis - Hong‐He Chen; Yu‐Xin Wang; De‐Feng Li; Chang Liu; Shuang‐Yu Bi; Cheng‐Ying Jiang; Shuang‐Jiang Liu (Environmental Microbiology, 2023)
Chemotaxis is crucial for bacterial adherence and colonization of the host gastrointestinal tract. Previous studies have demonstrated that chemotaxis affects the virulence of causative pathogens and the infection in the host. However, the chemotactic abilities of non‐pathogenic and commensal gut bacteria have rarely been explored. We observed that Roseburia rectibacter NSJ‐69 exhibited flagella‐dependent motility and chemotaxis to a variety of molecules, including mucin and propionate. A genome‐wide analysis revealed that NSJ‐69 has 28 putative chemoreceptors, 15 of which have periplasmic ligand‐binding domains (LBDs). These LBD‐coding genes were chemically synthesized and expressed heterologously in Escherichia coli . Intensive screening of ligands revealed four chemoreceptors bound to mucin and two bound to propionate. When expressed in Comamonas testosteroni or E. coli , these chemoreceptors elicited chemotaxis toward mucin and propionate. Hybrid chemoreceptors were constructed, and results showed that the chemotactic responses to mucin and propionate were dependent on the LBDs of R. rectibacter chemoreceptors. Our study identified and characterized R. rectibacter chemoreceptors. These results will facilitate further investigations on the involvement of microbial chemotaxis in host colonization.

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

The influence of MPL addition on structure, interfacial compositions and physicochemical properties on infant formula fat globules - Yibo Liu; Lu Liu; Shuming Liu; Meng Sun; Yang Jiao; Jing Chai; Lianji Bi; Awa Fanny Massounga Bora; Xiaodong Li; Xiuxiu Zhang; Bincheng Liu; Jinju Cheng; et al. (Food Research International, 2023)

Bipolar membrane electrodialysis combined with ozone oxidation wet scrubbing to remove SO2 and NO from flue gas and achieve CO2 mineralization - Yingying Zhao; Yupeng Cheng; Tingting Zhang; Shizhao Wang; Xiaofu Guo; Junsheng Yuan; Zhiyong Ji; Jie Liu; Fei Li; Jing Wang; Jingtao Bi (Fuel, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Performance characteristics and bacterial community analysis of a novel two-step-feed three-stage A/O-MBBR system for nitrogen removal in municipal wastewater - Xiaolin Zhou; Zijian Jiang; Jinzhao Gu; Xuejun Bi; Jingmiao Liu; Xuyi Wang; Tang Yang; Xueqing Shi; Lihua Cheng; Shujuan Huang; Xiaodong Wang; Harsha Ratnaweera; et al. (Journal of Water Process Engineering, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Effects of emulsifiers on heterocyclic amine formation and water distribution in roasted chicken patties - Asad Nawaz; Baoping Shi; Sana Irshad; Hao Suo; Xia Wang; Yuge Bi; Mingfu Wang; Feng Chen; Ka-Wing Cheng (Food Chemistry, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Activity characteristics of significant earthquake swarms in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2023)

Anaerobic co-digestion of three commercial bio-plastic bags with food waste: Effects on methane production and microbial community structure - Cheng Yu; Bi Dongsu; Zhang Tao; Jiang Xintong; Chen Ming; Wang Siqi; Shen Zheng; Zhang Yalei (Science of The Total Environment, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

Synthesis of crown ether-based microporous organic networks: A new type of efficient adsorbents for chlorophenols - Yi-Xuan Wang; Yan-Ping Bi; Yuan-Yuan Cui; Cheng-Xiong Yang (Journal of Hazardous Materials, 2023)

A flexible zinc ion hybrid capacitor integrated system with layers-dependent V2CTx MXene - Sairao Zhao; Xiao Luo; Yongfa Cheng; Zhixiang Shi; Tao Huang; Shanghua Yang; Haojian Zheng; Yun Bi; Jun Zhang; Qiuyue Shi; Minglei Cao; Chuankun Zhang; et al. (Chemical Engineering Journal, 2023)

Artificial intelligence technologies in bioprocess: Opportunities and challenges - Yang Cheng; Xinyu Bi; Yameng Xu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Bioresource Technology, 2023)

Melatonin ameliorates osteoarthritis rat cartilage injury by inhibiting matrix metalloproteinases and JAK2/STAT3 signaling pathway - Zhongyuan Zhao; Benjun Bi; Gong Cheng; Yuchi Zhao; Hao Wu; Mingdi Zheng; Zhilin Cao (Inflammopharmacology, 2023)

Electrostatic interaction and surface S vacancies synergistically enhanced the photocatalytic degradation of ceftriaxone sodium - Chen Zhang; Yingzhang Shi; Zhiwen Wang; Cheng Liu; Yidong Hou; Jinhong Bi; Ling Wu (Chemosphere, 2023)

Heatwave and urinary hospital admissions in China: Disease burden and associated economic loss, 2014 to 2019 - Yushu Huang; Hejia Song; Yibin Cheng; Peng Bi; Yonghong Li; Xiaoyuan Yao (Science of The Total Environment, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

High-throughput screening of metal–organic frameworks for hydrogen purification - Shihui Wang; Min Cheng; Lei Luo; Xu Ji; Chong Liu; Kexin Bi; Li Zhou (Chemical Engineering Journal, 2023)

Comparison of pulsed-field gel electrophoresis and a novel amplified intergenic locus polymorphism method for molecular typing of Campylobacter jejuni - Jin-Hong Liu; Cheng-Lu Lan; Ge-Feng Yao; Nian-Qing Kong; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Archives of Microbiology, 2023)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

An improved algae-YOLO model based on deep learning for object detection of ocean microalgae considering aquacultural lightweight deployment - Dan Liu; Pengqi Wang; Yuan Cheng; Hai Bi (Frontiers in Marine Science, 2022)
Algae are widely distributed and have a considerable impact on water quality. Harmful algae can degrade water quality and be detrimental to aquaculture, while beneficial algae are widely used. The accuracy and speed of existing intelligent algae detection methods are available, but the size of parameters of models is large, the equipment requirements are high, the deployment costs are high, and there is still little research on lightweight detection methods in the area of algae detection. In this paper, we propose an improved Algae-YOLO object detection approach, which is based on ShuffleNetV2 as the YOLO backbone network to reduce the parameter space, adapting the ECA attention mechanism to improve detection accuracy, and redesigning the neck structure replacing the neck structure with ghost convolution module for reducing the size of parameters, finally the method achieved the comparable accuracy. Experiments showed that the Algal-YOLO approach in this paper reduces the size of parameters by 82.3%, and the computation (FLOPs) is decreased from 16G to 2.9G with less loss of accuracy, and mAP by only 0.007 when compared to the original YOLOv5s. With high accuracy, the smaller model size are achieved, which reduces the equipment cost during actual deployment and helps to promote the practical application of algae detection.

Mitigation of low temperature stress by increased salinity is associated with multiple physiological responses in the gills of Takifugu fasciatus - Sisi Ma; Sheng Luo; Kai Zhang; Yuxi Liu; Xiaozhen Wei; Jinghao Cheng; Yihui Bi; Yiru Sun; Xinyu Zhang; Shaowu Yin; Tao Wang (Marine Biology, 2022)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Sharing of nitrogen between connected ramets of Alternanthera philoxeroides in homogeneous environments - Bi-Cheng Dong; Pu Wang; Fang-Li Luo (Plant and Soil, 2022)

Comprehensive Analysis of Aldehyde Dehydrogenases (ALDHs) and Its Significant Role in Hepatocellular Carcinoma - Senbang Yao; Wenjun Chen; He Zuo; Ziran Bi; Xiuqing Zhang; Lulian Pang; Yanyan Jing; Xiangxiang Yin; Huaidong Cheng (Biochemical Genetics, 2022)
Oxidative DNA damage is closely related to the occurrence and progression of cancer. Oxidative stress plays an important role in alcohol-induced hepatocellular carcinoma (HCC). Aldehyde dehydrogenase (ALDH) is a family of enzymes that plays an essential role in the reducing oxidative damage. However, how ALDHs family affects alcohol-related HCC remains obscure. We aimed to explore the correlation between the differential expression of ALDHs in patients with HCC and pathological features, as well as the relationship between ALDHs and prognosis, and finally analyze the possible mechanism of ALDHs in targeted therapy of HCC. The data of HCC were downloaded from The Cancer Genome Atlas (TCGA) database. This research explored the expression and prognostic values of ALDHs in HCC using Oncomine, UALCAN, Human Protein Atlas, cBioPortal, Kaplan–Meier plotter, GeneMANIA, Tumor Immune Estimation Resource, GEPIA databases, and WebGestalt. Low mRNA and protein expressions of ALDHs were found to be significantly associated with tumor grade and clinical cancer stages in HCC patients. In particular, the loss of ALDH expression is more obvious in Asians, and its effect on prognosis is far more significant than that in the White race. Our findings play an important role in the study of prognostic markers and anti-liver cancer therapeutic targets for the members of the ALDHs family, especially in patients with liver cancer in Asia.

Conspecific disturbance odors act as alarm cues to affect female mate choice in a treefrog - Ke Deng; Ya Zhou; Hao-Di Zhang; Qiao-Ling He; Bi-Cheng Zhu; Tong-Liang Wang; Ji-Chao Wang; Wouter Halfwerk; Jian-Guo Cui (Behavioral Ecology and Sociobiology, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Remelting of a Neoproterozoic arc root: origin of the Pulang and Songnuo porphyry Cu deposits, Southwest China - Dian-Zhong Wang; Ruizhong Hu; Pete Hollings; Xian-Wu Bi; Hong Zhong; Li-Chuan Pan; Cheng-Biao Leng; Ming-Liang Huang; Jing-Jing Zhu (Mineralium Deposita, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Detection and significance of exosomal mRNA expression profiles in the cerebrospinal fluid of patients with meningeal carcinomatosis - Peng Cheng; Feifei Feng; Hui Yang; Suqin Jin; Chao Lai; Yun Wang; Jianzhong Bi (Journal of Molecular Neuroscience, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Speciation Analysis of Chromium in Chromium-Enriched Yeast by Ion Chromatography-Inductively Coupled Plasma Mass Spectrometry - Shuang-Qing Zhang; Sui-Han Cheng; Shi Shen; Bi-Ying Luo; Yan Zhang (Biological Trace Element Research, 2021)

Alpinia oxyphylla–Schisandra chinensis Herb Pair Alleviates Amyloid-β Induced Cognitive Deficits via PI3K/Akt/Gsk-3β/CREB Pathway - Yu Qi; Huiting Jing; Xinhui Cheng; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (NeuroMolecular Medicine, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Fine mapping, candidate genes analysis, and characterization of a brown planthopper (Nilaparvata lugens Stål) resistance gene in the rice variety ARC5984 - Jiebin Lin; Xinyi Wang; Yang Li; Fanggui Bi; Ling Cheng; Fengkuang Huang; Rongbai Li; Yongfu Qiu (Euphytica, 2020)

Combination of schisandrin and nootkatone exerts neuroprotective effect in Alzheimer’s disease mice model - Yu Qi; Xinhui Cheng; Huiting Jing; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Genomic characterizations of H4 subtype avian influenza viruses from live poultry markets in Sichuan province of China, 2014–2015 - Chuansong Quan; Ting Huang; Xiuwei Chen; Jie Zhang; Qianli Wang; Cheng Zhang; Tiyan Zhang; Lijun Zhou; Liumei Shu; Chunrong Long; Lei Yang; Xunbo Du; et al. (Science China Life Sciences, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

Atmospheric deposition of polycyclic aromatic hydrocarbons (PAHs) in Shanghai: the spatio-temporal variation and source identification - Chen Cheng; Chunjuan Bi; Dongqi Wang; Zhongjie Yu; Zhenlou Chen (Frontiers of Earth Science, 2018)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

Reverse-time migration and amplitude correction in the angle-domain based on Poynting vector - Ji-Cheng Liu; Xiao-Bi Xie; Bo Chen (Applied Geophysics, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

The implication of salience network abnormalities in young male adult smokers - Yangding Li; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yanzhi Bi; Sha Shi; Ting Xue; Xiaoqi Lu; Wei Qin; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Neural correlates of 12-h abstinence-induced craving in young adult smokers: a resting-state study - Yangding Li; Kai Yuan; Yanzhi Bi; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Sha Shi; Xiaoqi Lu; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Altered resting state functional connectivity of anterior insula in young smokers - Yanzhi Bi; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Yangding Li; Dahua Yu; Wei Qin; Jie Tian (Brain Imaging and Behavior, 2017)

A Fluoro-Chromogenic Sensor Based on Organic Molecular Framework for Cu2+ and F− in Aqueous Soluble DMSO - Veikko Uahengo; Yan Zhang; Bi Xiong; Pingping Zhao; Ping Cai; Lydia Rhyman; Ponnadurai Ramasami; Kai Hu; Gongzhen Cheng (Journal of Fluorescence, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Programmed cell death in the cyanobacterium Microcystis aeruginosa induced by allelopathic effect of submerged macrophyte Myriophyllum spicatum in co-culture system - Yan He; Qiao-Hong Zhou; Bi-Yun Liu; Long Cheng; Yun Tian; Yong-Yuan Zhang; Zhen-Bin Wu (Journal of Applied Phycology, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Effects of Methyl Mercury Chloride on Rat Hippocampus Structure - Jingwei Wu; Guangyuan Cheng; Zhiyan Lu; Mingyue Wang; Jianying Tian; Yongyi Bi (Biological Trace Element Research, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

miR-137 suppresses the invasion and procedure of EMT of human breast cancer cell line MCF-7 through targeting CtBP1 - Yong Han; Yueyang Bi; Haiyang Bi; Caimei Diao; Guoqiang Zhang; Kai Cheng; Zhenlin Yang (Human Cell, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Reduced Expression of P2Y2 Receptor and Acetylcholinesterase at Neuromuscular Junction of P2Y1 Receptor Knock-out Mice - Miranda L. Xu; Cathy W.C. Bi; Lily K.W. Cheng; Shinghung Mak; Ping Yao; Wilson K.W. Luk; Kitty K.M. Lau; Anthony W.M. Cheng; Karl W.K. Tsim (Journal of Molecular Neuroscience, 2015)

Regulation of OPG and RANKL expressed by human dental follicle cells in osteoclastogenesis - Haiyan Sun; Qihong Li; Yongkuan Zhang; Yingchun Bi; Xia Li; Yao Shu; Xuepeng Chen; Zuolin Jin; Cheng Ge (Cell and Tissue Research, 2015)

Clonal integration in homogeneous environments increases performance of Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Qian Zhang; Fei-Hai Yu (Oecologia, 2015)

Satellite-Based Investigation and Evaluation of the Observational Environment of Meteorological Stations in Anhui Province, China - Yu-Bin Li; Tao Shi; Yuan-Jian Yang; Bi-Wen Wu; La-Bao Wang; Chun-E Shi; Jian-Xia Guo; Cheng-Li Ji; Hua-Yang Wen (Pure and Applied Geophysics, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Clinical assessment and polysomnographic study of sleep apnea in a Chinese population of snorers - Chuan Shao; Jing-bo Jiang; Hong-cheng Wu; Shi-bo Wu; Bi-yun Yu; Yao-dong Tang (Journal of Zhejiang University-SCIENCE B, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

NOTCH1 signaling promotes chemoresistance via regulating ABCC1 expression in prostate cancer stem cells - Cheng Liu; Zhuohang Li; Liangkuan Bi; Kuiqing Li; Bangfen Zhou; Chen Xu; Jian Huang; Kewei Xu (Molecular and Cellular Biochemistry, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Genetic diversity analysis of yellow mustard (Sinapis alba L.) germplasm based on genotyping by sequencing - Yong-Bi Fu; Bifang Cheng; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Relating hydrograph components to rainfall and streamflow: a case study from northern Taiwan - Yu-Ji Li; Shin-jen Cheng; Tsang-Long Pao; Yi-jie Bi (Hydrological Sciences Journal, 2012)

Effects of fragmentation on the survival and growth of the invasive, clonal plant Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Wei Guo; Fei-Hai Yu (Biological Invasions, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Proteomic analysis of cell lines to identify the irinotecan resistance proteins - Xing-Chen Peng; Feng-Ming Gong; Meng Wei; Xi Chen; Ye Chen; Ke Cheng; Feng Gao; Feng Xu; Feng Bi; Ji-Yan Liu (Journal of Biosciences, 2010)

How internode length, position and presence of leaves affect survival and growth of Alternanthera philoxeroides after fragmentation? - Bi-Cheng Dong; Guo-Lei Yu; Wei Guo; Ming-Xiang Zhang; Ming Dong; Fei-Hai Yu (Evolutionary Ecology, 2010)

Expression and Purification of an Antimicrobial Peptide, Bovine Lactoferricin Derivative LfcinB-W10 in Escherichia coli - Xingjun Feng; Chunlong Liu; Jiayin Guo; Chongpeng Bi; Baojing Cheng; Zhongyu Li; Anshan Shan; Zhongqiu Li (Current Microbiology, 2010)

Eleven novel microsatellite markers developed from the living fossil Ginkgo biloba (Ginkgoaceae) - Xiao-Ling Yan; Ye-Ye Chen; Bi-Cai Guan; Cheng-Xin Fu (Conservation Genetics, 2009)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Isolation and characterization of microsatellite markers in Dysosma versipellis (Berberidaceae), a rare endemic from China - Bi-Cai Guan; Ying-Xiong Qiu; Cheng-Xin Fu (Conservation Genetics, 2008)

Effect of erythromycin on metabolism of quetiapine in Chinese suffering from schizophrenia - Kun-Yan Li; Xin Li; Ze-Neng Cheng; Bi-Kui Zhang; Wen-Xing Peng; Huan-De Li (European Journal of Clinical Pharmacology, 2005)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)

The crystal structures of Phascolopsis gouldii wild type and L98Y methemerythrins: structural and functional alterations of the O2 binding pocket - Christopher S. Farmer; Donald M. Kurtz; Zhi-Jie Liu; Bi Cheng Wang; John Rose; Jingyuan Ai; Joann Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 2001)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)